Нарушение местного иммунитета и цитокинового статуса у больных генерализованным пародонтитом - Борисенко, Анатолій Васильович; Коленко, Юлія Генадіївна; Тімохіна, Тетяна Олександрівна (Actual Dentistry, 2019)
Objectives. Periodontal diseases represent a significant general medical and social problem. In the pathogenesis of generalized periodontitis an important role is played by the immune mechanisms of its development. Activation by parodontopathogenic microflora of monocytes and macrophages increases the production by these cells of proinflammatory cytokines, causing an imbalance between their proinflammatory and anti-inflammatory pools. It is believed that this is one of the main causes of injury of periodontal tissues, which may lead to the formation of periodontal pockets and resorption of alveolar bone of the jaw. Aim. The purpose of the work is to determine the level of immunoglobulin’s, cytokine’s production and circulating immune complexes in the oral fluid of patients with generalized parodontitis (GP). Materials and methods. To achieve this goal, 93 patients with GP were examined, aged 42 to 60 years old. The patients were divided into two groups: the first group consisted of 43 persons who were diagnosed with the GP II degree, and the second group was 50 patients with the GP of the third degree. The diagnosis and degree of severity of GP were established according to the classification of M.F. Danilevsky, 1994. All patients had an immunological examination, which included the determination of the level of pro- and antiinflammatory cytokines by the immune enzyme method, the level of circulating immune complexes (CICs) of different molecular weights, and the concentration of immunoglobulins (Ig G, Ig A, Ig M) in serum and saliva. Results. Patients with a GP of grade ІІІ (group 2) showed significantly higher values of the IR, PMA index and the index of hygiene, indicating a much more profound pattern of lesions of periodontal tissues. In the blood serum of patients with the GP of the III really higher Ig G and Ig M levels were found, significantly higher content of pathogenic CICs of medium and small, as well as a significantly lower concentration of physiological CICs of a large size. Changes in local oral immunity in patients with GP are of a pronounced and profound nature and directly proportional to the degree of the disease. Conclusions. In patients with generalized parodontitis, violations in the systemic and local links of the immune system are found, which are pronounced and depend on the severity of the disease. In patients with generalized parodontitis in the oral liquid, there is a marked imbalance of pro- and anti-inflammatory cytokines with a probable prevalence of TNF-α, IL-1β and IL-17А and a significantly higher IgG content, with a significantly reduced concentration of Sig A. Key words: generalized parodontitis, local immunity, cytokines, oral fluid, secretory immunoglobulin A, circulating immune complexe.